Weight Loss Effects of Once-Weekly Semaglutide 2.4 mg in Adults with and Without Type 2 Diabetes: A Systematic Review and Meta-Analysis - Boram Hong; Haesoo Kim; Daeun Lee; Kisok Kim (Pharmaceuticals)
Background/Objectives: Semaglutide, a glucagon-like peptide-1 receptor (GLP-1R) agonist, is a well-established pharmacologic agent for inducing weight loss in individuals with obesity and is prescribed regardless of type 2 diabetes mellitus (DM) status. However, it remains unclear whether the weight-lowering efficacy of semaglutide differs significantly between individuals with and without DM. To address this question, we conducted a systematic review and meta-analysis comparing the effects of once-weekly subcutaneous semaglutide at 2.4 mg on weight loss in adults with and without DM. Methods: A comprehensive literature search was performed using the PubMed database to identify randomized controlled trials (RCTs) involving overweight or obese adults receiving semaglutide at 2.4 mg weekly for 40 to 70 weeks. Using a random-effects model, we estimated the weighted mean differences in body weight reduction between the two groups. Nine RCTs met the inclusion criteria, among which two provided subgroup data for participants with and without DM within the same trial population. Registration number in PROSPERO: CRD420251077610. Results: In participants with DM (n = 4 studies), semaglutide was associated with a weighted mean body weight reduction of −6.34% (95% confidence interval: −6.98 to −5.69), with negligible heterogeneity across studies (I2 = 0.0%). By contrast, among participants without DM (n = 7 studies), the weighted estimate of weight loss was −11.57% (95% confidence interval: −12.94 to −10.19), with moderate heterogeneity observed (I2 = 63.6%). Conclusions: The observed difference in weight loss efficacy between the groups was clinically meaningful. While once-weekly semaglutide at 2.4 mg elicited significant weight loss in both populations, the magnitude of effect was notably greater in those without DM. This disparity may be explained by metabolic characteristics frequently present in individuals with DM, such as insulin resistance, hyperinsulinemia, and compensatory mechanisms related to glycemic control.